Variations in attack patterns between female and male outside hitters in top-level volleyball - Drikos, S.; Sotiropoulos, K.; Gkreka, S.; Tsakiri, M.; Barzouka, K. (International Journal of Sports Science & Coaching, 2023)
In volleyball outside hitters have wide participation in the offensive game. This study aims to analyze the variables that predict attack effectiveness in top-level volleyball depending on gender. Inferential statistics, multinomial logistic regression and multiple correspondence analysis were applied to analyze 1931 attacks (1154 for women and 777 for men) from the six top-ranked teams in the Men and Women World Championships 2018. The analysis revealed that the two genders vary in some aspects of the game at the top level. In order to increase the odds for a winning attack, male volleyball teams must pass the ball to the setter accurately, setting in 2nd fast tempo to zones 4 and 6, enriching offensive options across all the net to avoid attack against an organized block. On the other hand, female teams must set in 2nd fast tempo to the offensive zone (positions 4 & 2), to avoid off-speed attacks, to spike primarily parallel and to take advantage of no block situations. A similarity between genders is that attack against a single block is more difficult and causes lower effectiveness than spike versus open double block.